Determination of Toxin Properties and Toxicity Study of Horseshoe Crab in Kabong, Lundu and Miri Sarawak - Muhammad Zaid, Nasir (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Horseshoe crab belongs to the family of Limulidae known to possess a tetrodotoxin (TTX) which can cause horseshoe crab poisoning and adverse effect to human health. In current study, there are two species found in Sarawak which are Tachypleus gigas and Carcinoscorpius rotundicauda. The TTX concentration in soft tissue and eggs from Kabong, Lundu and Miri Sarawak were analyzed and determined by application of Thin Layer Chromatography (TLC), High Performance Liquid Chromatography and Liquid Chromatography-Mass Spectrometry (LC-MS). Some extracted toxin for all specimens were shown to be toxic while another were non-toxic. Among the tissues, eggs were found to be highest TTX concentration (5.40 MU/g) followed by the soft tissue (3.20 MU/g). Moreover, TTX concentrations among horseshoe crab species were different with C. rotundicauda showed highest TTX value (13.54 MU/g) which found in eggs while the lowest value was detected in T. gigas (3.59 MU/g). From this study, LC-MS method is the best tools to determine the TTX and suggested being used as procedure in screening of seafood for monitoring program. Furthermore, data of TTX levels in selected horseshoe crab from this study could be important information and uses as guideline in order to reduce and prevent horseshoe crab poisoning cases especially in Sarawak waters.